Histological features of malignancy correlate with growth patterns and patient outcome in lung adenocarcinoma. Issue 3 (16th June 2017) - Mäkinen, Johanna M; Laitakari, Kirsi; Johnson, Shirley; Mäkitaro, Riitta; Bloigu, Risto; Pääkkö, Paavo; Lappi‐Blanco, Elisa; Kaarteenaho, Riitta
Abstract : Aims: Until the launch of the International Association for the Study of Lung Cancer/American Thoracic Society/European Respiratory Society adenocarcinoma classification in 2011, there were no uniform histological grading criteria for pulmonary adenocarcinomas. The current classification highlights the prognostic importance of the various histological growth patterns observed in these morphologically heterogeneous neoplasias. In this study, we aimed to evaluate the classic histological parameters of malignancy in correlation with the growth patterns and patient outcomes in a series of 112 surgically operated stage I–IV lung adenocarcinomas. Methods and results: Architectural growth pattern analysis was performed according to the current adenocarcinoma classification. Histological features including, for example, nuclear atypia, mitotic activity, tumour necrosis, and different patterns of invasion were assessed and correlated statistically with the architecture and the clinical data. A solid predominant histology was associated with increased levels of atypia ( P  = 0.027), mitotic activity ( P  < 0.001), necrosis ( P  < 0.001), and lymphovascular invasion ( P  = 0.001), and a non‐predominant solid pattern was associated with intra‐alveolar tumour spread ( P  = 0.004). The presence of a non‐predominant lepidic tumour component showed inverse correlations with atypia ( P  = 0.002), mitotic rate ( P  = 0.009), and tumour necrosis ( P  < 0.001). Tumour size ( P  < 0.001), mitotic activity ( P  = 0.019), tumour necrosis ( P  = 0.002), lymphovascular invasion ( P  = 0.001) and visceral pleural involvement ( P  = 0.001) were all associated with reduced disease‐specific survival. Conclusions: The classic histological features of malignancy correlate with tumour architecture and patient outcome, confirming the prognostic value of the growth pattern analysis and questioning the need for a parallel grading system in pulmonary adenocarcinoma.